2022
DOI: 10.1093/mnras/stac1217
|View full text |Cite
|
Sign up to set email alerts
|

Dual AGN in the Horizon-AGN simulation and their link to galaxy and massive black hole mergers, with an excursus on multiple AGN

Abstract: The occurrence of dual active galactic nuclei (AGN) on scales of a few tens of kpc can be used to study merger-induced accretion on massive black holes (MBHs) and to derive clues on MBH mergers, using dual AGN as a parent population of precursors. We investigate the properties of dual AGN in the cosmological simulation Horizon-AGN. We create catalogs of dual AGN selected with distance and luminosity criteria, plus sub-catalogs where further mass cuts are applied. We divide the sample into dual AGN hosted in di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 63 publications
1
19
2
Order By: Relevance
“…There are three main possible explanations for a triple object: (1) a triple lensed system, that is, three images of the same object; (2) lensing of a dual AGN, in other words two distinct objects, one of which has two detected lensed images; and (3) a system of three different AGNs, a possibility predicted by current models (e.g., Ni et al 2022;Bhowmick et al 2020;Volonteri et al 2022) and previously observed in the local Universe (e.g., Pfeifle et al 2019;Foord et al 2021;Yadav et al 2021).…”
Section: J1608+2716mentioning
confidence: 99%
See 2 more Smart Citations
“…There are three main possible explanations for a triple object: (1) a triple lensed system, that is, three images of the same object; (2) lensing of a dual AGN, in other words two distinct objects, one of which has two detected lensed images; and (3) a system of three different AGNs, a possibility predicted by current models (e.g., Ni et al 2022;Bhowmick et al 2020;Volonteri et al 2022) and previously observed in the local Universe (e.g., Pfeifle et al 2019;Foord et al 2021;Yadav et al 2021).…”
Section: J1608+2716mentioning
confidence: 99%
“…Given the long merging timescale (∼1 Gyr, e.g., Tremmel et al 2017), a population of dual or multiple SMBHs must exist in many galaxies (Volonteri et al 2003). SMBHs are expected to accrete material from the merging host galaxies, producing dual or multiple luminous active galactic nuclei (AGNs) in the same galaxy (Steinborn et al 2016;Rosas-Guevara et al 2019;Volonteri et al 2022). For example, Volonteri et al (2022) estimate that at z > 2 more than 1% of the bright AGNs (L bol > 10 43 erg s −1 ) are expected to have a companion within 10 kpc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, only ∼0.1% of the triple systems at cosmic noon in ASTRID have L bol  10 45 erg s −1 for each member at r p < 40 kpc. Similarly, in the Horizon-AGN simulation, quadruple systems with each AGN brighter than L bol > 10 45 erg s −1 (like J1608) and separated by r p < 30 kpc only constitute ∼0.001% of the entire AGN population at z ∼ 2.5 (Volonteri et al 2022). The realistic probability of observing a luminous quadruple quasar system with r p  7 kpc (∼0 9) would be even lower.…”
Section: Multiple Quasars Triggered In Galaxy Mergers?mentioning
confidence: 94%
“…The luminosity used in this work to describe both AGNs is the rest-frame bolometric luminosity, with no correction for extinction or host galaxy contamination. We characterize the dAGN luminosity as the sum of the two bolometric luminosities (similar to Volonteri et al 2022, and other works in the literature) to provide a scale for the luminosity of the system. 9 We defer a careful analysis of the spectral properties of the two AGNs, and strategies to best detect them, to future work.…”
Section: Accretion Rates and Luminositiesmentioning
confidence: 99%